Patient and clinician's ratings of improvement in methadone-maintained patients: Differing perspectives? - Pérez de los Cobos José; Guàrdia Joan; Batlle Francisca; Iraurgi Ioseba; Siñol Núria; Trujols Joan (BMC, 2011)
Abstract Background In the last few years there seems to be an emerging interest for including the patients' perspective in assessing methadone maintenance treatment (MMT), with treatment satisfaction surveys being the most commonly-used method of incorporating this point of view. The present study considers the perspective of patients on MMT when assessing the outcomes of this treatment, acknowledging the validity of this approach as an indicator. The primary aim of this study is to evaluate the concordance between improvement assessment performed by two members of the clinical staff (a psychiatrist and a nurse) and assessment carried out by MMT patients themselves. Method Patients (n = 110) and their respective psychiatrist (n = 5) and nurse (n = 1) completed a scale for assessing how the patient's condition had changed from the beginning of MMT, using the Patient Global Impression of Improvement scale (PGI-I) and the Clinical Global Impression of Improvement scale (CGI-I), respectively. Results The global improvement assessed by patients showed weak concordance with the assessments made by nurses (Quadratic-weighted kappa = 0.13, p > 0.05) and by psychiatrists (Quadratic-weighted kappa = 0.19, p = 0.0086), although in the latter, concordance was statistically significant. The percentage of improved patients was significantly higher in the case of the assessments made by patients, compared with those made by nurses (90.9% vs. 80%, Z-statistic = 2.10, p = 0.0354) and by psychiatrists (90.9% vs. 50%, Z-statistic = 6.48, p < 0.0001). Conclusions MMT patients' perception of improvement shows low concordance with the clinical staff's perspective. Assessment of MMT effectiveness should also focus on patient's evaluation of the outcomes or changes achieved, thus including indicators based on the patient's experiences, provided that MMT aim is to be more patient centred and to cover different needs of patients themselves.